Changes in Body Composition of Senior Females Induced by Strength-Endurance Motor Program - Agata Horbacz; Alena Buková; Aurel Zelko (Jan Długosz University in Częstochowa, 2019)
The aim of work was to determine the effects of 8-week strength-endurance training program on somatic indicators in senior females. Applying bioelectrical impedance analysis method (InBODY 230 device) we evaluated the following parameters: body weight, BMI, body fat, total skeletal muscle mass, body fat percentage, skeletal muscle mass in left and right upper and lower extremities, trunk muscle mass, and the mineral mass in the body. To assess regularity of physical activities, variability of lifestyle and quality of life, we used a standardized survey questionnaire. The study was carried out on 29 senior citizens, of the average 70.28 years of age and BMI 26.47 kg/m2. A group of active elderly women underwent an 8-week strength-endurance program, including exercises focused primarily on the development of strength abilities of the upper limbs, and secondarily on developing strength abilities of lower extremities and developing general aerobic abilities. The influence of the aerobic program induced statistically significant increase in the total skeletal muscle mass from the initial value of 22.966 kg to 23.552 kg, an increase by 0.552kg (p ≤ 0.01) of the monitored parameter. On the contrary, the parameter of body fat percentage of the studied group showed significant decrease of the input value of 36.207%, to the output value of 35.062%, representing a change at the level of 1.145% (p ≤ 0.01). By assessment of changes in the muscle mass of upper limbs and the trunk, we found a statistically significant increase, which reflects a change in the total quantity of the skeletal muscle (p ≤ 0.005). The mineral mass in the probands increased by only 0.091 kg. However, this increase was confirmed at 0.1% level of statistical significance (p ≤ 0.001). The above results indicate that regular performance of physical activities in groups of the elderly proves to be efficient in preventing sarcopenia, obesity and maintaining a balance of the particular tissues making up the total body composition.